Somewhere only we know - Goo, Maurene (Farrar, Straus and Giroux, 2019)
Told from two viewpoints, teens Lucky, a very famous K-pop star, and Jack, a part-time paparazzo who is trying to find himself, fall for each other against the odds through the course of one stolen day.